Risky Sex in Rural America: Longitudinal Changes in a Community-Based Cohort of Methamphetamine and Cocaine Users - Borders, Tyrone F. (2013)
BACKGROUND AND OBJECTIVES: This study examined the longitudinal associations between stimulant use and sexual behaviors. METHODS: Data are from a 3-year community-based study of 710 rural stimulant users. Past 30-day crack cocaine, powder cocaine, and methamphetamine use and sexual behaviors (any sex, inconsistent condom use, and multiple sexual partners) were assessed through in-person interviews every 6 months. RESULTS: GEE analyses revealed that the odds of having sex remained steady over time, with crack cocaine and methamphetamine use positively associated with having sex. The odds of multiple sexual partners declined, but the odds of inconsistent condom use remained steady over time. Crack cocaine use was positively associated with multiple sexual partners, whereas powder cocaine use was negatively associated with inconsistent condom use. DISCUSSION AND CONCLUSIONS: Many rural stimulant users could potentially benefit from safe sex educational programs. Such efforts could reduce the incidence of HIV and other STIs in rural America.